Accounting essentials for hospitality managers - Guilding, Chris; Mingjie Ji, Kate (Routledge, Taylor & Francid Group, 2022)
"For non-accountant hospitality managers, accounting and financial management is often perceived as an inaccessible part of the business. Yet having a grasp of accounting basics is a key part of management. Using an 'easy-to-read' style, this book provides a comprehensive overview of the most relevant accounting techniques and information for hospitality managers. It demonstrates how to organise and analyse accounting data to help make informed decisions with confidence. With its highly practical approach, this new 4th Edition: Quickly develops the reader's ability to adeptly use and interpret accounting information to enhance organisational decision making and control. Demonstrates how an appropriate analysis of financial reports can drive your business strategy forward from a well-informed base. Presents new accounting problems in the context of a range of countries and currencies throughout. Develops mastery of the key accounting concepts through financial decision making cases that take a hospitality manager's perspective on a range of issues. Includes accounting problems at the end of each chapter to be used to test knowledge and apply understanding to real life situations. Offers extensive web support for instructors and students that includes PowerPoint slides, solutions to end of chapter problems, test bank and additional exercises. The book is written in an accessible and engaging style and structured logically with useful features throughout to aid students' learning and understanding. It is a key resource for all future hospitality managers"--